A pilot study to assess the feasibility and accuracy of using haptic technology to occlude digital dental models. (March 2016) - Wu, Wen; Cen, Yuhai; Hong, Yang; Keeling, Andrew; Khambay, Balvinder
Abstract: Objectives: The use of haptic technology as an adjunct to clinical teaching is well documented in medicine and dentistry. However its application in clinical patient care is less well documented. The aim of this pilot study was to determine the feasibility and accuracy of using a haptic device to determine the occlusion of virtual dental models. Methods: The non-occluded digital models of 20 pre-treatment individuals were chosen from the database of Faculty of Dentistry, The University of Hong Kong. Following minimal training with the haptic device (Geomagic ® Touch™), the upper model was occluded with the lower model until a stable occlusion was achieved. Seven landmarks were placed on each of the corners of the original and haptically aligned upper model bases. The absolute distance between the landmarks was calculated. Intra- and inter-operator errors were assessed. Results: The absolute distance between the 7 landmarks for each original and corresponding haptically aligned model was 0.54 ± 0.40 mm in the x -direction (lateral), 0.73 ± 0.63 mm in the y -direction (anterior–posterior) and 0.55 ± 0.48 mm in the z -direction (inferior–superior). Conclusion: Based on initial collision detection to prevent interpenetration of the upper and lower digital model surfaces, and contact form resistance during contact, it is possible to use a haptic device to occlude digital study models. Clinical Significance: The use of 3D digital study models is routine, but new problems arise, such as the lack of "touch" in a virtual environment. Occluding study models requires the sense of touch. For the first time, using haptic technology, it is possible to occlude digital study models in a virtual environment.